Stemona alkaloid derivative induce ferroptosis of colorectal cancer cell by mediating carnitine palmitoyltransferase 1 - Yang, He; Wang, Ling; Zhang, Mengcheng; Wu, Xingkang; Li, Zhenyu; Ma, Kaiqing (Frontiers in Chemistry, 2024)
Accumulation of acylcarnitines is a characteristic feature of various metabolic disorders affecting fatty acid metabolism. Despite extensive research, no specific molecules have been identified to induce ferroptosis through the regulation of acylcarnitine metabolism. In this study, acylcarnitine accumulation was identified based on cell metabolomics study after the treatment with Stemona alkaloid derivative (SA-11), which was proved to induce ferroptosis in our previous research. Furthermore, the CPT-1 level was proved to significantly increase, while the CPT-2 level indicated no significant difference, which resulted in the accumulation of acylcarnitine. Besides, the ferroptosis-inducing ability of SA-11 was significantly enhanced by the addition of exogenous acylcarnitine, presumably due to the production of additional ROS. This hypothesis was corroborated by the observation of increased ROS levels in HCT-116 cells treated with SA-11 compared to the control group. These findings suggest that targeting acylcarnitine metabolism, particularly through CPT-1, may offer a novel therapeutic strategy for cancer treatment by enhancing ferroptosis induction.